2006
DOI: 10.4278/0890-1171-20.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Yogic Breathing and Meditation Intervention for Individuals Living with HIV/AIDS

Abstract: In order to capture the outcomes of this program properly, both qualitative and quantitative measures are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 9 publications
(6 reference statements)
2
46
0
1
Order By: Relevance
“…More specifically, whilst respondents who scored high on the SWLS lend support to Brazier et al's [23] research findings showing a strong correlation between yoga practice and high levels of satisfaction with life, those who expressed high ratings on the SHS offer consistency with the results of Ghoncheh and Smith's [24] study, in which practitioners reported boosted energy and enjoyment levels as a result of their practice.…”
Section: Yoga Practice and Psychological Wellbeingsupporting
confidence: 71%
See 1 more Smart Citation
“…More specifically, whilst respondents who scored high on the SWLS lend support to Brazier et al's [23] research findings showing a strong correlation between yoga practice and high levels of satisfaction with life, those who expressed high ratings on the SHS offer consistency with the results of Ghoncheh and Smith's [24] study, in which practitioners reported boosted energy and enjoyment levels as a result of their practice.…”
Section: Yoga Practice and Psychological Wellbeingsupporting
confidence: 71%
“…More specifically, whilst some have revealed that yoga practice correlates with high levels of life satisfaction others have highlighted the effects of yoga in boosting vitality and enjoyment levels [23,24]. In terms of eudemonic wellbeing, research appears to support the notion that yoga practice can promote significant increases in meaning in life.…”
Section: Yoga Practice and Psychological Wellbeingmentioning
confidence: 84%
“…For example, YM can improve symptoms of stress, anxiety, depression and pain, drug dependence, and QOL and alter disease progression. 1,29,53 The current report appears to be the first on the effect of YM in PLWH crack cocaine users, and the results are consistent with the literature.…”
Section: Yoga Qol and Stress In Hiv-positive Crack Userssupporting
confidence: 89%
“…YM is increasingly being used to manage symptoms and risk factors associated with many chronic diseases, 17,18 such as cancer, 19,20 diabetes, 21 hypertension, 22 cardiovascular disease, 23 and AIDS. [24][25][26][27][28] Studies in PLWH showed that YM decreased pain and anxiety, 1,29 increased CD4 T lymphocytes independently of ART, 30 increased CD2 + counts, 31 improved overall survival rates, 32 and increased motivation for drug abstinence and HIV prevention behaviors. 33 A large body of evidence suggests that HIV and ART, along with drug abuse, lead to a wide spectrum of abnormalities in immunologic, neurologic, and neuroendocrine systems, even during the asymptomatic phase of infection.…”
mentioning
confidence: 99%
“…Individuals infected with HIV can use healthy behaviors to enhance their physical and emotional well-being (Brazier, Mulkins, & Verhoef, 2006;Galantino et al, 2005;Inouye, Flannelly, & Flannelly, 2001;Ironson et al, 2005;Miles et al, 2003); however, engaging in a new healthy behavior can be challenging. In general, HIV-infected women report high levels of stress that may complicate the use of healthy behaviors (Catz, Gore-Felton, & McClure, 2002;Gray & Cason, 2002;Riley & Fava, 2003).…”
mentioning
confidence: 99%